Plasma N‐acylethanolamine and endocannabinoid levels in burning mouth syndrome: Potential role in disease pathogenesis. (2nd March 2018) - Barry, Alison; O'Halloran, Ken D.; McKenna, Joseph P.; McCreary, Christine; Harhen, Brendan; Kerr, Daniel M.; Finn, David P.; Downer, Eric J.
Abstract : Objective: The objective was to measure endocannabinoid (eCB) ligands and non‐cannabinoid N‐acylethanolamine (NAE) molecules in plasma from individuals with burning mouth syndrome (BMS) and to determine whether plasma eCB/NAE levels correlated with pain, inflammation and depressive symptomatology in this cohort. Study Design: Plasma content of the eCBs, anandamide (AEA) and 2‐arachidonoyl‐glycerol (2‐AG), and the NAE molecules, palmitoylethanolamide (PEA) and oleoylethanolamide (OEA) were assessed in healthy subjects (n = 8) and in a cohort of newly diagnosed BMS patients (n = 9) using liquid chromatography‐tandem mass spectrometry. Plasma eCBs and NAE profiles were correlated with self‐rated oral cavity pain intensities, depressive symptomatology and plasma IL‐8 levels. Results: Plasma levels of PEA, but not OEA, AEA or 2‐AG, were significantly elevated in patients with BMS, when compared to plasma from healthy individuals. Plasma PEA, OEA and AEA levels correlated with depressive symptomatology. Conclusions: This is the first evidence to indicate that circulating eCB/NAE levels are altered in BMS.